A hybrid fuzzy SWARA-COPRAS framework to evaluate sustainable co-firing in coal power plants: A case study from Indonesia - Dana Utama; Berlinda Diami (Jurnal Sistem dan Manajemen Industri, 2025)
The transition to sustainable energy encourages various countries, including Indonesia, to adopt Co-Firing technology to reduce carbon emissions without requiring significant investments in power plant infrastructure. The selection of appropriate biomass materials, based on sustainability dimensions, significantly influences the success of Co-Firing implementation. This study proposes a hybrid framework that integrates the Fuzzy SWARA and Fuzzy COPRAS methods to holistically evaluate Co-Firing alternatives, considering technical, economic, environmental, social, and supply chain aspects. A case study was conducted at a power plant in Indonesia, involving four experts from the industry and academia to assess 23 sustainability sub-criteria and five biomass alternatives. The results indicate that the sub-criteria of water footprint, supplier reliability, local job creation, and co-firing retrofit cost are dominant factors in biomass selection. This research selected Alternative 2 (wood chips) as the most effective biomass material for implementation at power plants in Indonesia. Additionally, sensitivity analysis confirmed that biomass is the most stable alternative to changes in criteria weights, which offers high flexibility in the supply chain and circular economic potential. These findings contribute theoretically to developing multi-criteria decision-making methods based on fuzzy logic and practically support policymakers and industry in planning sustainable and adaptive Co-Firing strategies in the face of uncertainty.